Waist circumference and waist-to-height ratio of Hong Kong Chinese children - Kwok Charlotte WL; Yin Jane AT; Li Albert M; Nelson Edmund AS; Choi Kai-Chow; So Hung-Kwan; Sung Rita YT; Ng Pak-Cheung; Fok Tai-Fai (BMC, 2008)
Abstract Background Central body fat is a better predictor than overall body fat for cardiovascular (CV) risk factors in both adults and children. Waist circumference (WC) has been used as a proxy measure of central body fat. Children at high CV risk may be identified by WC measurements. Waist-to-height ratio (WHTR) has been proposed as an alternative, conveniently age-independent measure of CV risk although WHTR percentiles have not been reported. We aim to provide age- and sex-specific reference values for WC and WHTR in Hong Kong Chinese children. Methods Cross sectional study in a large representative sample of 14,842 children aged 6 to 18 years in 2005/6. Sex-specific descriptive statistics for whole-year age groups and smoothed percentile curves of WC and WHTR were derived and presented. Results WC increased with age, although less after age 14 years in girls. WHTR decreased with age (particularly up to age 14). WHTR correlated less closely than WC with BMI (r = 0.65, 0.59 cf. 0.93, 0.91, for boys and girls respectively). Conclusion Reference values and percentile curves for WC and WHRT of Chinese children and adolescents are provided. Both WC and WHTR are age dependent. Since the use of WHRT does not obviate the need for age-related reference standards, simple WC measurement is a more convenient method for central fat estimation than WHRT.